2005
DOI: 10.1152/jn.00976.2004
|View full text |Cite
|
Sign up to set email alerts
|

Optically Recorded Response of the Superficial Dorsal Horn: Dissociation From Neuronal Activity, Sensitivity to Formalin-Evoked Skin Nociceptor Activation

Abstract: . The OIS DR decreases under FAcϩGln, whereas the P-PSP DR remains unaltered; under 4-AP, the P-PSP DR increases, but the OIS DR decreases. In contrast, both the OIS DR and P-PSP DR increase when K ϩ o is elevated to 8 mM. These observations from slices from normal subjects are interpreted to indicate that the OIS DR mainly reflects cell volume and light scattering changes associated with DH s astrocyte uptake of K ϩ and glutamate (GLU). In slices from subjects that received an intracutaneous injection of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…1B) failed to significantly alter either the magnitude or time course of the reduction of the OIS DR that followed exposure to FC. Consistent with the demonstration that magnitude of the OIS DR depends on glutamatergic neurotransmission [4, 21], APV application alone led to a modest suppression of the OIS DR (plot with gray squares at Fig. 1B) that reversed and returned to control levels 20~25 min after the perfusion solution was restored to drug-free, normal ACSF.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…1B) failed to significantly alter either the magnitude or time course of the reduction of the OIS DR that followed exposure to FC. Consistent with the demonstration that magnitude of the OIS DR depends on glutamatergic neurotransmission [4, 21], APV application alone led to a modest suppression of the OIS DR (plot with gray squares at Fig. 1B) that reversed and returned to control levels 20~25 min after the perfusion solution was restored to drug-free, normal ACSF.…”
Section: Resultssupporting
confidence: 83%
“…Observations reported in previous studies are fully consistent with the idea that impairment of the ability of astrocytes to regulate extracellular K + and glutamate levels alters excitatory neurotransmission at multiple levels of the CNS. As examples: (1) the secondary hyperalgesia that follows intradermal injection of 5% formalin is accompanied by an impaired ability of astrocytes to regulate [K + ] o and [glutamate] o in the region of the DH s that receives its input from the injected skin site [4, 5], (2) even a brief (40 sec) increase in extracellular K + induces LTP in the hippocampal slice [6]; (3) hippocampal LTP is substantially reduced in animals in which astrocytes are rendered unable (via a selective genetic manipulation) to release neurotransmitters [7]; (4) d-serine released from astrocytes is critical for the induction of LTP in hippocampal slices [8]; (4) the slow astrocytic depolarization that accompanies hippocampal LTP is due to astrocyte uptake of K + and supports neuronal LTP by reducing the efficacy of astrocytic glutamate transporters and inducing astrocyte release of a variety of signaling molecules (for review see [9]); and, finally, (5) intracerebral injection of fluorocitrate (a reversible, selective inhibitor of glial metabolism, [5, 10]) elevates [K + ] o , increases cortical neuron excitability, and induces focal epileptiform discharge [11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we regarded this very slow decay of the OIS as having little or no physiological significance. This interpretation proved premature, however, because in vitro studies carried out in parallel with our in vivo studies (Kohn et al, 2000;Lee et al, 2005) revealed that the OIS, while providing an accurate indication of the locus and magnitude of local neuronal activation, is not directly attributable to neuronal activity. Instead, our studies of spinal cord and sensorimotor cortical slices convincingly revealed that the OIS is the result of astrocytic swelling due to uptake (along with water) of the excess extracellular K+ and neurotransmitters (e.g., glutamate) released during excitatory neurotransmission.…”
Section: Extended Exposure To Stimulationmentioning
confidence: 86%
“…The OIS obtained using infrared light has been shown to be highly correlated with light scattering effects that accompany astrocyte swelling subsequent to the clearance of extracellular K + and neurotransmitter [14,15,18] and local increases in blood volume [19,20]. Although the OIS at this wavelength may be influenced by changes in hemoglobin concentration and oxygenation, it is likely that contributions from these factors are small when compared with light scattering effects[20].…”
Section: Discussionmentioning
confidence: 99%